Coagulation System in Various Diseases (Eurasian Research Bulletin, 2023)
Recent advancements in anesthetic practice have led to a deeper understanding of the blood coagulation system. It is important to recognize that coagulation is a dynamic process. While the traditional categorization into extrinsic and intrinsic pathways remains relevant, recent insights provide a more precise depiction. The pro-coagulant pathway, responsible for initiating clot formation, is intricately balanced by mechanisms that restrict its spread beyond the site of injury in the normal coagulation process. Critical illness or the perioperative phase can disrupt this balance, potentially resulting from various underlying conditions that heighten the risk of either bleeding or thrombosis. Through a comprehensive search of the different literature using MeSH terms such as "coagulation system, haemostasis, and anesthesia," twenty-eight interconnected clinical trials and review articles from the past decade were identified. It is imperative for clinicians to grasp the physiological underpinnings of hemostasis in order to effectively diagnose and address coagulation abnormalities. This understanding is also crucial for interpreting diagnostic tests related to coagulation, as the equilibrium of the coagulation system can tip towards bleeding or thrombosis in various clinical scenarios.